2012
DOI: 10.1007/s00428-012-1245-8
|View full text |Cite
|
Sign up to set email alerts
|

Histological examination and evaluation of donor bile ducts received during orthotopic liver transplantation—a morphological clue to ischemic-type biliary lesion?

Abstract: Ischemic-type biliary lesions (ITBL) belong to a group of biliary disorders that are regarded as the major complication in patients with orthotopic liver transplantation (OLT). We performed histological evaluation of donor common bile ducts received during OLT to find morphological clues to the pathomechanisms of ITBL. We investigated 93 grafts of 92 patients (recipients: mean age, 56.5 years; underlying disease: hepatocellular carcinoma (n = 45), alcoholic cirrhosis (n = 16), viral hepatitis with cirrhosis (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 12 publications
7
113
0
Order By: Relevance
“…Recently, 3 independent clinical studies have demonstrated that major mucosal cell loss (>50% biliary epithelial injury) and mural stroma necrosis (<50% necrotic cells) of the large bile duct is present in more than 80% of human donor livers (both DBD and DCD) at the end of SCS and subsequent reperfusion. 4,24,27 Although biliary preservation injury is apparently almost universally present, only a minority ) concentration and pH detected in bile. Biliary bicarbonate concentrations were significantly higher in livers that had been preserved by end-ischemic HMP, COR, or SNMP compared to livers that underwent only SCS (*P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, 3 independent clinical studies have demonstrated that major mucosal cell loss (>50% biliary epithelial injury) and mural stroma necrosis (<50% necrotic cells) of the large bile duct is present in more than 80% of human donor livers (both DBD and DCD) at the end of SCS and subsequent reperfusion. 4,24,27 Although biliary preservation injury is apparently almost universally present, only a minority ) concentration and pH detected in bile. Biliary bicarbonate concentrations were significantly higher in livers that had been preserved by end-ischemic HMP, COR, or SNMP compared to livers that underwent only SCS (*P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin-embedded slides of extrahepatic bile ducts were prepared for H&E staining and complementary staining with periodic acid-Schiff after diastase digestion. Slides of the extrahepatic bile ducts were graded according to a systematic scoring system of bile duct injury as first described by Hansen et al (14). All liver and bile duct slides were examined by an experienced liver pathologist (ASH Gouw) using light microscopy.…”
Section: Histological Evaluationmentioning
confidence: 99%
“…After reperfusion, the production of reactive oxygen species, cytokines secretion, neutrophil infiltration and the impaired hepatic microcirculation provoke inflammation, cell death, loss of functioning parenchyma and ultimately organ failure (36,37). Moreover, cholangiocytes are more susceptible to IRI and extended damage of the biliary epithelium is visible at the end of preservation of virtually all grafts (38,39). Peribiliary vascular plexus and glands (containing the precursor's niche) are also damaged by microthrombi and necrosis, leading to impaired regeneration of the biliary epithelium (40).…”
Section: Dcdmentioning
confidence: 99%